United States : Financial Sector Assessment Program-Technical Note-Risk Analysis and Stress Testing the Financial Sector. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
The U.S. financial system is very large, well-diversified, and home to numerous financial institutions which are significant at a global scale. Eight Global Systemically Important Banks (G-SIBs) are incorporated in the U.S., as well as several other large financial institutions, such as asset managers, insurers, and money market funds. Assets of the financial system amounted to about USD 100 trillion at end-2019 and accounted for 500 percent of GDP. While the eight G-SIBs dominate the U.S. banking landscape, banking system assets represent only about 22 percent of total financial system assets. The systemic risk assessment (including stress testing) of this FSAP reflect the highly diversified nature of the U.S. financial system and focuses on banks, mutual and money market funds, insurance companies as well as cross-institutional and cross-sectoral linkages and exposures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet